2018
DOI: 10.1002/ange.201800130
|View full text |Cite
|
Sign up to set email alerts
|

Der präexponentielle Faktor in der Elektrochemie

Abstract: Wie in vielen Zweigen der Wissenschaft, um nicht von der Kultur im Allgemeinen zu reden, so gibt es auch in der Elektrochemie eine Reihe von wiederkehrenden Themen: Forschungsgebiete, die eine Zeit lang populär sind, dann verblassen, wenn ihre Möglichkeiten erschöpft scheinen, um Jahrzehnte später wieder aktuell zu werden, wenn Fortschritte in experimentellen oder theoretischen Techniken neue Forschungsmöglichkeiten eröffnen. Ein gutes Beispiel sind Brennstoffzellen, die fünf solcher Zyklen durchlaufen haben; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
(101 reference statements)
0
2
0
Order By: Relevance
“…This has, unfortunately, remained unattainable due to theoretical and methodological difficulties and omissions. [25] Surprisingly, a general GCE rate theory has not yet been established; mending this deficiency is the central goal of the present work.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…This has, unfortunately, remained unattainable due to theoretical and methodological difficulties and omissions. [25] Surprisingly, a general GCE rate theory has not yet been established; mending this deficiency is the central goal of the present work.…”
Section: Introductionmentioning
confidence: 95%
“…In particular, both vibronic and electronic non-adiabatic effects are frequently encountered in outer-sphere and long-range ET, PT, and PCET reactions. [25,33] Even for electrocatalytic reactions, non-adiabaticity may be present and the importance and contribution of non-adiabaticity may depend on the electrode potential. [34,35] As a concrete example, it has been shown that only the inclusion of vibronic non-adiabaticity in electrochemical hydrogen evolution reaction can explain experimentally observed Tafel slopes and kinetic isotope effects.…”
Section: Introductionmentioning
confidence: 99%